Knock limit prediction via multi-zone modelling of a primary reference fuel HCCI engine. (27th August 2010) - Tzanetakis, Tommy; Singh, Priyanka; Chen, Ju-Tsung; Thomson, Murray J.; , Charles R. Koch
A multi-zone model was used to predict the combustion behaviour of a single cylinder Homogeneous Charge Compression Ignition (HCCI) engine. Blow-by was considered to capture engine performance at the low operating speed of 700 rpm. The model was calibrated and verified by matching predicted and experimental pressure traces at two engine operating points. The calculated CO and Unburned Hydrocarbon (UHC) emissions showed good agreement with experiments at both points. The onset of knock during HCCI was adequately reproduced using the Maximum Pressure Rise Rate (MPRR) criterion and another method based on the pressure equalisation rate within the charge.